(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Design and Characteristics of Embeddedsystems are playing an increasingly important role in control engineering.Despite their popularity, embedded systems are generally subject to resourceconstraints and it is therefore difficult to build complex control systems onembedded platforms. The impact ofautomation is visible in all areas of industry as well as in everyday life.Automation makes the process control more efficient, increases productivity ofwork, manufacturing quality, decreases manufacturing costs. Automation is stillin development so that it could succeed in filling all requirements of today’stechnical advance. For this reason we daily meet new questions aboutimplementation of automation systems, their handling and expanding. One ofthese is the question of communication in industrial applications. In case ofhaving more PLCs in one industrial network, it is necessary to solve theirinter-communication. We should deal with this question in dependence on somefacts, for example: used control system, used industrial network, transmissionreliability requirements and so on. In this article we would like to present asolution for intercommunication between PLCs in one industrial networkcommunication. A programmable logiccontroller (PLC) is a small embedded computer used for automation of real-worldprocesses, such as control of machinery on factory assembly lines. The programcontrols the complex sequences required in modern manufacturing automation.